Comparação entre a aplicação e não aplicação do LED (Light Emitted Diode) na cicatrização de pacientes submetidas e abdominoplastia - Ramos, Renato Franz Matta (2017)
Introduction: Cicatrization is a tissue response to damage, an inflammatory process or cell necrosis. The LED (Light Emitted Diode) is a topic phototherapy that can improve the wound healing process. Objective: To compare the cicatrization with and without the use of LED in patients underwent abdominoplasty. Methods: A double-blinded, non-controlled, non-randomized clinical trial. There were included patients who underwent abdominoplasty between 2014 and 2016 from the plastic surgery department. After 48 hours the LED treatment began, applying it only in the right side, every other day for ten sessions. The monofilament test was applied at days 2, 4, 6, 14 and 21. After one a six months, there were applied the Vancouver and Draaijers scales by two independent observers. At sixth month post-operative, there were taken standardized photographs of the scars and other two independent observers evaluated them. At twelve months post-operative, the patients responded two questionnaires about the aesthetic and sensitivity result of the scars. Results: There were 23 patients who underwent this surgery, 17 had complete evaluations and follow-up (lost of 26%). Only 14 (82%) patients had standardized photographs. After one year, just the 65% (11 patients) answered the questionnaires. When analyzing the final result of the scar at six months according the Vancouver and Draaijers scales, it was obtained a major numeric value to the left side (no treated side), it corresponded to a worst scar (p=0.003). It was obtained a less pain and uncomfortable sensation in all patients at sixth month post-operative with the monofilaments test, more frequently in the treated right side. According the standardized photographs, the right side was chosen as better scar aesthetically (p=0.008). Finally, according the questionnaires, there were no differences in the aesthetic (p=0.083) and sensitivity (p=0.564) results between the two sides. Conclusions: Cicatrization with the use of LED was better on the treated side according to the Vancouver and Draaijers scales and the standardized photographs. The monofilaments test showed a global improvement. The patients didn’t find differences on the aesthetic and the sensitivity results after one-year post-operative.